# simple but vexing, evaluating algebraic expressions: a = 4 b = -3 a – b^2

#### unclematt3

##### New member
simple but vexing, evaluating algebraic expressions: a = 4 b = -3 a – b^2

Scratching my head on this one.
a = 4 b = -3

a – b2

I maintain that the way to solve this is
(4) – (-3)2
4 – (9)
-5

My colleague says the following is correct
(4) – (-3)2
4 + 32
13

Please let me know what is the right answer, my way or my colleague's way.

Thank you!

#### Subhotosh Khan

##### Super Moderator
Staff member
Scratching my head on this one.
a = 4 b = -3

a – b2

I maintain that the way to solve this is
(4) – (-3)2
4 – (9)
-5

My colleague says the following is correct
(4) – (-3)2
4 + 32
13

Please let me know what is the right answer, my way or my colleague's way.

Thank you!

#### mmm4444bot

##### Super Moderator
Staff member
Here's one way to explain the mistake, to your colleague. When we square a negative number, the "negative part" gets squared, too. (The negative sign in -3 represents a factor of -1.)

In other words:

-3 = (-1)(3)

Therefore:

(-3)^2 = (-1)^2 ∙ (3)^2 = (1)(9) = 9

This is why all squares are non-negative numbers. So, subtracting b^2 means subtracting positive 9, like you did. :cool:

#### Dr.Peterson

##### Elite Member
Scratching my head on this one.
a = 4 b = -3

a – b2

I maintain that the way to solve this is
(4) – (-3)2
4 – (9)
-5

My colleague says the following is correct
(4) – (-3)2
4 + 32
13

Please let me know what is the right answer, my way or my colleague's way.

Thank you!
You didn't state how your colleague was thinking, but possibly he saw two negatives in a row and thought they cancel, as they would in 4 - (-3). The trouble here is that in between them, logically, there is a squaring, which changes the sign. Ultimately, this would be an "order of operations" issue.

Last edited: